Predicting Distress in Islamic Banks: The Effectiveness of Capital Measures in CAMELS Framework - Khokher, Zahid ur Rehman; Alhabshi, Syed Musa bin Syed Jaafar (Journal of Reviews on Global Economics, 2019)
This study aims to identify key capital adequacy measures and other parameters that effectively predict distress in Islamic banks taking a panel of 65 banks from 13 countries between 2008-2017 using logistic regression model. The paper also intends to see whether simpler ratios perform better than more complex, risk weighted measures in predicting distress in these banks. A total of nine alternative capital and leverage indicators are used in the model that mainly rely on financial and accounting data, which are supplemented by the addition of market leverage for listed banks. In order to capture variability in cross country analysis and impact of economic conditions and shocks, the study also adds several macroeconomic indicators in the model. The results suggest that most of the standard CAMELS indicators are relevant for studying distress in Islamic banks. Further, it is shown that three other capital ratios – Tier 1, tangible common ratio and market leverage - are equally effective in studying Islamic bank failures. The findings, however, reflect that Basel III leverage ratio and other accounting-based ratios do not offer effective early warning signals of Islamic bank stress. Overall, equity based risk-weighted capital ratios offer a more robust framework of regulation and supervision in Islamic banks.